Effects of a 25-week periodized training macrocycle on muscle strength, power, muscle architecture, and performance in well-trained track and field throwers - Anousaki, E.; Zaras, N.; Stasinaki, A. N.; Panidi, I.; Terzis, G.; Karampatsos, G. (The Journal of Strength and Conditioning Research, 2021)
The purpose of the study was to investigate the effect of a 25-week macrocycle on strength, power, vastus lateralis (VL) muscle architecture, and competitive track and field throwing performance, in well-trained track and field throwers. Twelve well-trained throwers (age: 24.3 ± 5.5 years, mass: 96.6 ± 9.9 kg, and height: 1.82 ± 0.02 m), participated in the study. All athletes followed a 25-week periodized training program divided into 3 training phases: the hypertrophy/maximum strength phase, the maximum strength/power phase, and the power/speed phase. Measurements were performed at the beginning of the training period (T1), after the first training phase (T2), and after the end of the training period (T3). Measurements included the following: competitive track and field throwing performance; shot put throws; maximum strength (1-RM) in snatch, clean, and squat; countermovement jump (CMJ); and VL muscle architecture. Competitive track and field throwing performance and shot put throws increased from T1 to T3 by 10.9 ± 3.2% (p = 0.001) and 5.1 ± 6.4% (P = 0.049), respectively. 1 RM strength in snatch and squat increased significantly from T1 to T3 by 9.7 ± 8.9% (p = 0.001) and 9.9 ± 7.1% (p = 0.002), respectively. Countermovement jump height increased only from T1 to T2 by 10.9 ± 11.8% (p = 0.026). A significant increase was found for VL fascicle length between T1 and T3 (9.6 ± 11.1%, p = 0.049). Strong correlations were found between the percentage increase of competitive track and field throwing performance with 1 RM snatch (r = 0.571, p = 0.046) and with shot put throws (r = 0.715, p = 0.001). Twenty five weeks of training may increase performance and VL fascicle length, whereas increases in 1 RM snatch and in shot put throws are associated with competitive track and field throwing performance in well-trained throwers.